2002
DOI: 10.1046/j.1432-1033.2002.03151.x
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of coenzyme B12‐dependent glycerol dehydratase in complex with cobalamin and propane‐1,2‐diol

Abstract: Recombinant glycerol dehydratase of Klebsiella pneumoniae was purified to homogeneity. The subunit composition of the enzyme was most probably a 2 b 2 c 2 . When (R)-and (S)-propane-1,2-diols were used independently as substrates, the rate with the (R)-enantiomer was 2.5 times faster than that with the (S)-isomer. In contrast to diol dehydratase, an isofunctional enzyme, the affinity of the enzyme for the (S)-isomer was essentially the same or only slightly higher than that for the (R)-isomer (K m(R) /K m(S) ¼… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
142
1
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 103 publications
(155 citation statements)
references
References 55 publications
(74 reference statements)
9
142
1
3
Order By: Relevance
“…There are four helpful examples: glutamate mutase (PDB ID code 1I9C) from Clostridium cochlearium (10), methylmalonyCoA mutase (MMCoA mutase) from P. shermanii (9) (PDB ID code 1REQ), diol dehydratase (40) (PDB ID codes 1DIO and 1EEX), and glycerol dehydratase (PDB ID code 1IWP) from Klebsiella pneumoniae (41). Interactions of cobalamin with these proteins all follow a pattern in which the methyl groups of rings C and D, at the hydrophobic rim of the corrin macrocycle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…There are four helpful examples: glutamate mutase (PDB ID code 1I9C) from Clostridium cochlearium (10), methylmalonyCoA mutase (MMCoA mutase) from P. shermanii (9) (PDB ID code 1REQ), diol dehydratase (40) (PDB ID codes 1DIO and 1EEX), and glycerol dehydratase (PDB ID code 1IWP) from Klebsiella pneumoniae (41). Interactions of cobalamin with these proteins all follow a pattern in which the methyl groups of rings C and D, at the hydrophobic rim of the corrin macrocycle (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Inability to form these hybrid complexes might be partly due to the loss of mutual interaction between heterologous ␣D and ␥G subunits, because the homologous ␣ and ␥ subunits form a tight complex (components S and A in diol dehydratase (6) and glycerol dehydratase (7), respectively). Tight interactions between ␣ and ␥ subunits were revealed by the X-ray structures of diol and glycerol dehydratases (7,24). Co-existence and mutual interaction of ␣ and ␥ subunits are required for correct folding of diol dehydratase (6).…”
Section: Production and Distribution Of The Hybrid Enzymes Between DImentioning
confidence: 99%
“…These regions of ␤ and ␥ subunits of diol dehydratase lower the solubility of diol dehydratase ( 23 ). The X-ray structures ( 7,24,25 ) revealed that both enzymes exist as ( ␣␤␥ ) 2 complexes whose overall structures are strikingly similar. The structures of the active sites of both enzymes are also similar-that is, the K ϩ ion is bound in the inner part of the so-called TIM (triose phosphate isomerase) barrel of the ␣ subunit, and the two hydroxyl groups of substrate 1,2-propanediol are directly coordinated to this K ϩ ion.…”
mentioning
confidence: 97%
See 2 more Smart Citations